Hand Hygiene Practices among Nurses in South Sulawesi Hospitals - Muhammad Rizky Asfarada; Rini Rachmawaty; Andina Setyawati; Gulzar Malik (Media Kesehatan Masyarakat Indonesia, 2024)
Healthcare professionals’ adherence to hand hygiene protocols is paramount to prevent Healthcare-Associated Infections (HAIs) and ensure patient safety. This study evaluates compliance with the World Health Organization's (WHO) "Five-Moment Hand Hygiene" protocol among nurses in two Indonesian hospitals: Regional General Hospital X in Makassar City and Provincial General Hospital Y in South Sulawesi Province. A total of 60 nurses participated, with demographic analysis revealing significant differences between the hospitals. Utilizing a comprehensive observation tool provided by the WHO, data analysis indicated variations in hand hygiene practices, particularly after touching patient surroundings. Despite these differences, the data followed a normal distribution, enhancing the reliability of statistical analyses. Significant disparities in hand hygiene practices were found after touching patient surroundings (p-value = 0.008; α < 0.05), underscoring the urgent need for targeted interventions among nurses to improve their compliance and enhance patient safety. This study recommends comprehensive training, resource provision, regular audits, fostering a supportive organizational culture, and integrating robust hand hygiene modules into nursing education. The study also suggests further research to identify barriers and improvement strategies. Addressing these recommendations collectively will bolster patient safety and reduce healthcare-associated infection burdens in Indonesian healthcare settings. The study's identification of specific deficiencies in hand hygiene practices provides actionable insights for healthcare administrators, infection control practitioners, and frontline healthcare workers, emphasizing the urgency of sustained efforts to promote proper hand hygiene practices.